Educational anxiety among university students in Iceland : association with gender and educational level - Hanna Lára Harðardóttir 1993- (2017)
The purpose of the study was to examine the effects of gender and educational level on anxiety related to education, among university students in Iceland. The study was conducted by an online questionnaire, which included demographic questions, questions about anxiety and the shorter version of the Depression Anxiety Stress Scale (DASS21). A total of 123 university students participated in the study, there of 95 females and 28 males. The age range of the participants was from 19-57 years old, and they were either studying for a bachelor degree or a master degree. Results showed that 84.5% of the students experienced moderate to very great anxiety related to their education, with almost 18% who reported very great anxiety. Female students reported on average greater anxiety related to their education compared to male students, and those studying for a bachelor degree reported more educational anxiety on average than those studying for a master degree. The main effects of gender and educational level were though, not significant. No significant interaction between gender and educational level on anxiety related to education was found. Keywords: Anxiety, university students, college students, mental disorder. Markmið rannsóknarinnar var að kanna möguleg áhrif kyns og námsstöðu á kvíða tengdum námi, meðal íslenskra háskólanemenda. Rannsóknin var framkvæmd með spurningakönnun á internetinu, sem innihélt bakgrunnsspurningar, spurningar um kvíða einstaklinga og styttri útgáfuna af Þunglyndis, kvíða og streitu-kvarðanum (e. Depression Anxiety Stress Scale; DASS21). Alls tóku 123 háskólanemendur þátt í rannsókninni, þar af 95 konur og 28 karlar. Þátttakendur voru á aldursbilinu 19-57 ára, og voru annað hvort í grunnnámi eða framhaldsnámi. Niðurstöður sýndu að 84,5% þátttakanda upplifðu miðlungs til mjög mikils kvíða í tengslum við nám sitt, þar sem tæplega 18% sögðust upplifa mjög mikinn kvíða. Að meðaltali greindu konur frá meiri kvíða við nám sitt en karlar, og þeir þátttakendur sem voru í grunnnámi greindu frá meiri ...